Relationship Between Nurses' Hand Washing Compliance by Fuerbringer and The Incidence of Nosocomial Infection in Surgical Room - Ulum, Bahrul; Retno, Retno Twistiandayani; Roshida, Devy Syanindita (Jurnal Surya, 2025)
Introduction: Surgical site infection (SSI) is an infection that often occurs in post-surgery patients, this occurs because nurses' handwashing compliance is still not perfect according to the Fuerbringer handwashing principle, especially before performing surgical assistance. The impact of SSI causes serious complications, prolongs hospitalization, and increases health care costs. Methods: This study used a cross-sectional approach. The population was all nurses in the surgical room. The sampling technique used a non-probability purposive sampling type of 25 respondents. Data collection was carried out using a compliance questionnaire and observation of SSI infections. The independent variable is compliance with Fuerbringer handwashing. The dependent variable is the incidence of nosocomial infections. This study was analyzed using the Spearman Rank Rho test with a significance level of α <0.05. Results: The Spearman rank analysis test obtained a value of 0.000 (p-value <0.05) which means that there is a relationship between Nurses' handwashing compliance with Fuerbringer and the incidence of nosocomial infections in the surgical room. Conclusion: High handwashing compliance helps prevent cross-contamination between patients and nurses, which can reduce the risk of infection that can be obtained during hospital care. Keywords: Fuerbringer, Handwashing compliance, Nosocomial Infection